Prevalences of scabies and pediculosis corporis among homeless people in the Paris region: results from two randomized cross‐sectional surveys (HYTPEAC study). (30th November 2015) - Arnaud, A.; Chosidow, O.; Détrez, M.‐A.; Bitar, D.; Huber, F.; Foulet, F.; Le Strat, Y.; Vandentorren, S.
Summary: Background: Dermatological infections constitute the most common health problem in the homeless population. Objectives: To estimate the prevalences of scabies and pediculosis corporis and to identify associated factors in the homeless population. Methods: Two randomized cross‐sectional surveys were performed, one on the homeless population sleeping in public places in Paris, and the other on the homeless population in various shelters in the Ile‐de‐France administrative region. Overall 341 and 667 people, respectively, were interviewed about sociodemographic characteristics, lifestyle and hygiene practices, and were examined by a nurse. Results: In individuals sleeping in public places the prevalence of scabies was estimated at 6·5% [95% confidence interval (CI) 0·5–12·5] and for pediculosis corporis at 5·4% (95% CI 1·7–9·1). For those sleeping in shelters these values were 0·4% (95% CI 0·1–1·8) and 0·15% (95% CI 0·0–9·7), respectively ( P  <   0·01 in both cases). In public places, after multivariate analysis, being a woman, citing squats among the three main types of accommodation and not possessing a sleeping bag were significantly associated with diagnosis of scabies. Likewise, begging, a history of pubic lice, and not taking showers in municipal baths were associated with pediculosis corporis in public places. Conclusions: Firstly, this study highlights the real existence of two distinct subpopulations having different sociodemographic characteristics, with specific lifestyles and practices, and with different prevalences of ectoparasitism. Secondly, the results of the multivariate analyses will help the implementation of specific actions targeting the group of people who sleep in public places. Abstract : What's already known about this topic? Ectoparasitism is frequent among homeless persons, and is documented mainly in sheltered people. Little is known about ectoparasitism and hygiene conditions among homeless people sleeping in public places. What does this study add? The prevalence of ectoparasitism is higher in homeless people sleeping in public places than in sheltered persons. These results encourage further efforts to maintain the low‐level prevalence of ectoparasitism in people in shelters and underline the need for the implementation of targeted prevention interventions for people sleeping in public places.